Yield and fruit size distribution of processing tomato cultivars - Grilli, G. V G [UNESP]; Cintra, A. A D [UNESP]; Santos, G. M. [UNESP]; Braz, L. T. [UNESP]; Braz, B. A. (My University, 2004)
The productivity and fruit size distribution of 28 processing tomato cultivars were analyzed to determine the ones with potential for fresh market. The experiment was done in Jaboticabal-SP, Brazil (21o15'22'' South, 48o18'58'' West, altitude 595 m), in a Haplorthox soil, from June to December. The cultivars H 7155, Hypeel 108, Andino, U 573, H 9036, Ipa 6, H 9494, AG 33, Yuba, RPT 1294, AG 72, Peelmech, Curicó, Hypeel 45, RPT 1478, H 9492, H 9498, H 2710, Hitech 45, Halley, Botu 13, H 9553, U 646, NK 1570, AG 45, RPT 1095, RPT 1570 and PSX 37511 were evaluated. The experimental design was randomized blocks, with four repetitions, and five plants per experimental unit. Fruits harvested from each experimental unit were counted, classified by transversal diameter (large, medium, small, very small and cull) and then weighed. Cultivars AG 72, H 9498, Hypeel 45, RPT 1095 and Curicó yielded more than 70 fruits per plant, on average. The total production per plant of cultivars AG 72, H 9498, Hypeel 45, H 7155, Hypeel 108, Halley, Hitech, RPT 1095, H 9494, H 9036 and Curicó was greater than 4 kg. Considering the weight of large and medium fruits, categories which are important for fresh market, the cultivars H 2710, Botu 13, U 573, Hypeel 45, Yuba, RPT 1294 and Ipa 6 presented values above 50% for production.
Keywords: Fruit quality; Industrial processing; Lycopersicon esculentum Mill.; Yield